Extrusion molding silicon carbide material as well as preparation method and application thereof

By preparing an extruded silicon carbide material containing components such as water reducer and dispersant, the problem of cracking of silicon carbide material during drying is solved, moldability and product performance are improved, and equipment wear and energy consumption are reduced.

CN119638430APending Publication Date: 2025-03-18JIAGENG (JIANGSU) SPECIAL MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411856978.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Silicon carbide extrusion molding materials are prone to cracking during drying, and the amount of adhesive and plasticizer added is difficult to control, which can easily lead to equipment damage.

Method used

The raw material components including silicon carbide powder, carbon black, water reducing agent, dispersant, adhesive, plasticizer, lubricant and solvent are prepared through a specific mixing and kneading process to improve moldability and reduce the risk of cracking.

Benefits of technology

Effectively prevent the silicon carbide green body from cracking when drying, reduce equipment wear, improve product performance, and save energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638430A_ABST
    Figure CN119638430A_ABST
Patent Text Reader

Abstract

The invention provides an extrusion-molded silicon carbide material as well as a preparation method and application thereof. The extrusion-molded silicon carbide material provided by the invention comprises the following raw material components in parts by weight: 90-98 parts by weight of silicon carbide powder; 2 parts by weight to 10 parts by weight of carbon black; 2-4 parts by weight of a water reducing agent; 1.5 to 3.5 parts by weight of a dispersant; 2-4 parts by weight of an adhesive; 1.5 to 3.5 parts by weight of a plasticizer; 0.2 to 0.8 part by weight of a lubricant; 10 parts by weight to 20 parts by weight of a solvent; wherein the water reducing agent comprises a sulfonated polystyrene water reducing agent and a polycarboxylic acid water reducing agent; based on the total mass of the water reducing agent, the content of the sulfonated polystyrene water reducing agent is 25-55%, and the content of the polycarboxylic acid water reducing agent is 45-75%. The extrusion-molded silicon carbide material can solve the problem of drying cracking of a silicon carbide material green body, and abrasion to equipment is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of silicon carbide ceramics, and in particular to an extruded silicon carbide material and a preparation method and application thereof. Background Art

[0002] Silicon carbide extrusion molding is a process that uses adhesives and plasticizers to make silicon carbide plastic, and extrude silicon carbide materials through mechanical force. The principle of silicon carbide extrusion molding is: under the action of the extruder, the silicon carbide material passes through the extrusion port of the extruder and the internal space of the mold to finally form the required product shape. The advantages of silicon carbide extrusion molding are: the surface of the extruded product is smooth and the precision is high; the extruded product has a compact structure and light weight; the extruded product can save materials and save costs; after extrusion molding, silicon carbide needs to be dried to further shape it.

[0003] In the existing technology, since silicon carbide is a barren raw material with no viscosity, 3%-5% adhesive and 1%-2% plasticizer need to be added during extrusion molding to make it plastic. However, the amount of adhesive and plasticizer added is difficult to control and has a great impact. Too little will make it difficult to mold, and too much will make the clay hard, which is easy to cause damage to the equipment and is prone to deformation and cracking when the green body is drying. Summary of the invention

[0004] Based on the above problems, the present invention provides an extruded silicon carbide material and a preparation method and application thereof. The extruded silicon carbide material of the present invention can solve the problem of cracking of the green silicon carbide material during drying and avoid wear on the equipment.

[0005] The first aspect of the present invention provides an extruded silicon carbide material, comprising the following raw material components in parts by weight:

[0006] 90 to 98 parts by weight of silicon carbide powder;

[0007] 2 to 10 parts by weight of carbon black;

[0008] 2 to 4 parts by weight of water reducing agent;

[0009] 1.5 to 3.5 parts by weight of dispersant;

[0010] 2 to 4 parts by weight of adhesive;

[0011] 1.5-3.5 parts by weight of plasticizer;

[0012] Lubricant 0.2-0.8 parts by weight;

[0013] 10 to 20 parts by weight of solvent;

[0014] Wherein, the water reducer includes sulfonated polystyrene water reducer and polycarboxylic acid water reducer;

[0015] Based on the total mass of the water reducer, the content of the sulfonated polystyrene water reducer is 25% to 55%, and the content of the polycarboxylic acid water reducer is 45% to 75%.

[0016] A second aspect of the present invention provides a method for preparing an extruded silicon carbide material, wherein the extruded silicon carbide material is the extruded silicon carbide material according to the first aspect of the present invention, and the method comprises the following steps:

[0017] The first step is to put the silicon carbide powder and the carbon black into a mixer and mix them for 1 to 2 hours;

[0018] The second step is to add the water reducing agent, the dispersant, the adhesive, the plasticizer, the lubricant and the solvent to the material obtained in the first step, and then knead the mixture for 1 to 3 hours using a kneader to obtain a slurry;

[0019] The third step is to age the clay obtained in the second step for more than 6 hours;

[0020] The fourth step is to use a vacuum mud making machine to make mud with the mud material aged in the third step;

[0021] The fifth step is to extrude the material obtained in the fourth step through an extruder and then dry it.

[0022] The third aspect of the present invention is the use of the extruded silicon carbide material described in the first aspect of the present invention or the extruded silicon carbide material prepared by the method for preparing the extruded silicon carbide material described in the second aspect of the present invention in the preparation of silicon carbide ceramics by reaction sintering or pressureless sintering.

[0023] Through the above technical solution, the present invention has at least the following beneficial effects compared with the prior art:

[0024] The water reducer added to the extruded silicon carbide material provided by the present invention includes a sulfonated polystyrene water reducer and a polycarboxylic acid water reducer. Both of these water reducers can reduce the water content in the raw material components, thereby preventing the silicon carbide green body from cracking during drying and reducing its breakage rate. In addition, the extruded silicon carbide material provided by the present invention also has the functions of lubrication and grinding aid, reducing the wear on the equipment and saving the energy consumption of product preparation.

[0025] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram of an extruded silicon carbide material after drying according to an embodiment of the present invention.

[0027] Figure 2 A schematic diagram of a pair of proportional extruded silicon carbide materials after drying provided by the present invention. DETAILED DESCRIPTION

[0028] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0029] The first aspect of the present invention provides an extruded silicon carbide material, comprising the following raw material components in parts by weight:

[0030] 90 to 98 parts by weight of silicon carbide powder;

[0031] 2 to 10 parts by weight of carbon black;

[0032] 2 to 4 parts by weight of water reducing agent;

[0033] 1.5 to 3.5 parts by weight of dispersant;

[0034] 2 to 4 parts by weight of adhesive;

[0035] 1.5 to 3.5 parts by weight of plasticizer;

[0036] 0.2 to 0.8 parts by weight of lubricant;

[0037] 10 to 20 parts by weight of solvent;

[0038] Illustratively, the content of the silicon carbide powder can be 90 parts by weight, 91 parts by weight, 92 parts by weight, 93 parts by weight, 94 parts by weight, 95 parts by weight, 96 parts by weight, 97 parts by weight, or 98 parts by weight.

[0039] For example, the content of the carbon black may be 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, or 10 parts by weight.

[0040] For example, the content of the water reducing agent may be 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, or 4 parts by weight.

[0041] For example, the content of the dispersant may be 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, or 3.5 parts by weight.

[0042] For example, the content of the adhesive may be 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, or 4 parts by weight.

[0043] For example, the content of the plasticizer may be 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, or 3.5 parts by weight.

[0044] For example, the content of the lubricant may be 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, or 0.8 parts by weight.

[0045] Illustratively, the content of the solvent can be 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, or 20 parts by weight.

[0046] Exemplarily, the content of the sulfonated polystyrene water reducer can be 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, or 45%.

[0047] Exemplarily, the content of the polycarboxylate water reducer is 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, and 55%.

[0048] Wherein, according to the extruded silicon carbide material of the present invention, the water reducer comprises a sulfonated polystyrene water reducer and a polycarboxylic acid water reducer;

[0049] Based on the total mass of the water reducer, the content of the sulfonated polystyrene water reducer is 25% to 55%, and the content of the polycarboxylic acid water reducer is 45% to 75%.

[0050] Exemplarily, the content of the sulfonated polystyrene water reducer can be 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 50%, or 55%.

[0051] Exemplarily, the content of the polycarboxylate water-reducing agent can be 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 60%, 65%, 70%, or 75%.

[0052] The water reducer added to the extruded silicon carbide material provided by the present invention includes a sulfonated polystyrene water reducer and a polycarboxylic acid water reducer. Both of these water reducers can reduce the water content in the raw material components. This is because the water reducer molecules of the sulfonated polystyrene water reducer and the polycarboxylic acid water reducer will be adsorbed on the surface of the raw material particles of silicon carbide powder and carbon black, which can reduce the adsorption capacity of water on the surface of the particles, so that more water is in a free-flowing state, delaying the initial hydration reaction, thereby reducing the water consumed in the hydration reaction in the early stage, so that the water content in the silicon carbide material is higher, thereby preventing the silicon carbide green body from cracking during drying and reducing its breakage rate.

[0053] In addition, the sulfonated polystyrene water reducer and the polycarboxylic acid water reducer added to the extruded silicon carbide material provided by the present invention also have certain lubricating and grinding aid effects. This is because when the water reducer molecules of the sulfonated polystyrene water reducer and the polycarboxylic acid water reducer are adsorbed on the surface of the raw material particles of silicon carbide powder and carbon black, a layer of solvated water film is formed. The water film can provide a buffering effect for the raw material particles, reduce the friction between the raw material particles, and improve the dispersibility of the mud, thereby reducing the wear on the equipment and saving the energy consumption of product preparation.

[0054] Further, sulfonated polystyrene water reducer is a linear polymer with polystyrene as the main chain. The molecular chain contains a benzene ring structure, which is relatively rigid, giving the sulfonated polystyrene water reducer molecule a certain structural stability and rigid shape characteristics, so when its content in the silicon carbide material is too much, it will aggravate the cracking phenomenon of the silicon carbide green body, but the content of the sulfonated polystyrene water reducer should not be too little, otherwise it will affect the molding of the silicon carbide green body. The main chain of the polycarboxylic acid water reducer is generally composed of carbon atoms connected by carbon-carbon chains, and the molecular structure of the sulfonated polystyrene water reducer is relatively flexible. Moreover, different side chain structures are often connected to the main chain of the polycarboxylic acid water reducer to form a comb-like or branched molecular structure. This structure can make the polycarboxylic acid water reducer molecule have a large spatial stretchability in the solution, control the molecular hydrophilicity and steric hindrance effect to a certain extent, and play a role in dispersing the raw material particles, but its excessive content will affect the molding of the silicon carbide green body.

[0055] Based on this, the present invention simultaneously adds a sulfonated polystyrene water reducer and a polycarboxylic acid water reducer to the silicon carbide material, and controls the contents of the sulfonated polystyrene water reducer and the polycarboxylic acid water reducer. When the polycarboxylic acid water reducer and the sulfonated polystyrene water reducer are used together, the dispersibility of the sulfonated polystyrene water reducer molecules in the raw material particles can be improved, and the problem of cracking of the green body caused by the uneven distribution of the rigid structure molecules is avoided. At the same time, the presence of the sulfonated polystyrene water reducer and the improvement of its dispersibility improve the structural stability of the silicon carbide material, making the silicon carbide green body easier to shape and not damaged, thereby further improving the product performance of the extruded silicon carbide material.

[0056] In a specific embodiment, based on the total mass of the water reducer, the content of the sulfonated polystyrene water reducer is 28% to 50%; the content of the polycarboxylic acid water reducer is 50% to 70%.

[0057] Furthermore, according to the extruded silicon carbide material of the present invention, the mass ratio of the sulfonated polystyrene water reducer to the polycarboxylic acid water reducer is 1:(0.85-2.2), and illustratively, the mass ratio of the sulfonated polystyrene water reducer to the polycarboxylic acid water reducer can be 1:0.85, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.1, 1:2.2. By controlling the mass ratio of the two water reducers within a suitable range, the product performance of the extruded silicon carbide material can be further improved, the cracking of the blank can be improved, and the wear on the equipment can be reduced. In a preferred embodiment, the mass ratio of the sulfonated polystyrene water reducer to the polycarboxylic acid water reducer is 1:(1.1-1.9).

[0058] According to the extruded silicon carbide material of the present invention, the content of sulfonic acid groups in the sulfonated polystyrene water reducer is 25% to 28%. Exemplarily, the content of sulfonic acid groups in the sulfonated polystyrene water reducer can be 25%, 25.3%, 25.5%, 25.7%, 26%, 26.3%, 26.5%, 26.7%, 27%, 27.3%, 27.5%, 27.7%, 28%. Sulfonated polystyrene water reducer contains a certain amount of sulfonic acid groups, and the sulfonic acid groups have strong water solubility. When the water reducer molecules are adsorbed on the surface of the raw material particles of silicon carbide powder and carbon black, the sulfonic acid groups in the water reducer molecules attached to the surfaces of different raw material particles can form a strong Coulomb force in water, making the force between the raw material particles stronger, thereby further improving the structural stability of the silicon carbide material. However, when the content of sulfonic acid groups in the sulfonated polystyrene water reducer is excessive, the free flow state of water will be affected, causing the hydration reaction to consume too much water, resulting in a lower water content in the silicon carbide material. Therefore, the present invention helps to balance the structural characteristics and functional group characteristics of the water reducer molecule by further controlling the content of sulfonic acid groups, thereby making the silicon carbide green body easier to shape and not break, thereby further improving the product performance of the extruded silicon carbide material.

[0059] According to the extruded silicon carbide material of the present invention, the content of the carboxylic acid group in the polycarboxylic acid water reducer is 30% to 50%. Exemplarily, the content of the carboxylic acid group in the polycarboxylic acid water reducer can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%. The carboxylic acid group and the sulfonic acid group in the polycarboxylic acid water reducer have the same effect. When the water reducer molecules are attached to the surface of the raw material particles, they can play a role in enhancing the interaction between the raw material particles. Moreover, the dispersion degree of the polycarboxylic acid water reducer molecules is better, and the effect of the carboxylic acid group in the silicon carbide material is more obvious. Therefore, it is necessary to control the content of the carboxylic acid group in the polycarboxylic acid water reducer to avoid affecting the water content in the silicon carbide material, thereby further improving the product performance of the extruded silicon carbide material.

[0060] Further, according to the extruded silicon carbide material of the present invention, the mass ratio of the sulfonic acid group to the carboxylic acid group in the water reducer is 1: (1.5-2.5), and exemplary, the mass ratio of the sulfonic acid group to the carboxylic acid group can be 1: 1.5, 1: 1.6, 1: 1.7, 1: 1.8, 1: 1.9, 1: 2, 1: 2.1, 1: 2.2, 1: 2.3, 1: 2.4, 1: 2.5. The present invention can better adjust the relative content of the sulfonic acid group and the carboxylic acid group in the silicon carbide material by controlling the mass ratio of the sulfonic acid group to the carboxylic acid group. The introduction of sulfonic acid groups and carboxylic acid groups can enhance the interaction between the raw material particles. However, compared with the carboxylic acid group, the introduction of the sulfonic acid group may make the molecule more rigid, reduce the rotational freedom within the molecule, and the sulfonic acid group will be more acidic than the carboxylic acid group, which is easy to have a certain effect on the product properties of the formed silicon carbide green body. Therefore, it is necessary to control the mass ratio of sulfonic acid groups to carboxylic acid groups within an appropriate range to minimize the adverse effects of the joint use of the two water reducers.

[0061] In a preferred embodiment, the mass ratio of the sulfonic acid group to the carboxylic acid group in the water reducer is 1:(1.8-2.2).

[0062] According to the extruded silicon carbide material of the present invention, the particle size of the silicon carbide powder is 10 μm to 80 μm. Exemplarily, the particle size of the silicon carbide powder can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, and the silicon carbide powder includes a first silicon carbide powder, a second silicon carbide powder and a third silicon carbide powder;

[0063] The particle size of the first silicon carbide powder is 60 μm to 80 μm. For example, the particle size of the first silicon carbide powder can be 60 μm, 65 μm, 70 μm, 75 μm, or 80 μm. The particle size of the second silicon carbide powder is 35 μm to 55 μm. For example, the particle size of the second silicon carbide powder can be 35 μm, 40 μm, 41 μm, 42 μm, 43 μm, or 44 μm. , 45μm, 46μm, 47μm, 48μm, 49μm, 50μm, 55μm; the particle size of the third silicon carbide powder is 5μm to 25μm. For example, the particle size of the third silicon carbide powder can be 5μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 25μm. The third silicon carbide powder with a small particle size can fill the gap of the first silicon carbide powder with a large particle size. The present invention can make the formed silicon carbide ceramics denser by setting the silicon carbide powder to be a mixture of three silicon carbide powders with different particle sizes, and further improve the product performance of the extruded silicon carbide material.

[0064] In a preferred embodiment, the particle size of the first silicon carbide powder is 65 μm to 75 μm, the particle size of the second silicon carbide powder is 40 μm to 50 μm, and the particle size of the third silicon carbide powder is 10 μm to 20 μm.

[0065] According to the extruded silicon carbide material of the present invention, based on the total mass of the silicon carbide powder, the mass content of the first silicon carbide powder is 15% to 25%. Exemplarily, the mass content of the first silicon carbide powder can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, or 25%.

[0066] According to the extruded silicon carbide material of the present invention, based on the total mass of the silicon carbide powder, the mass content of the second silicon carbide powder is 32.5% to 42.5%. Exemplarily, the mass content of the second silicon carbide powder can be 32.5%, 33%, 33.5%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, or 42.5%.

[0067] According to the extruded silicon carbide material of the present invention, based on the total mass of the silicon carbide powder, the mass content of the third silicon carbide powder is 37% to 46.5%. Exemplarily, the mass content of the third silicon carbide powder can be 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, or 46.5%.

[0068] The content of silicon carbide powder with a larger particle size is higher, which will lead to larger gaps between particles, so that the density of silicon carbide materials is reduced. The content of silicon carbide powder with a smaller particle size is higher, which will make reactive sintering and siliconization difficult, and easily cause cracking of the silicon carbide blank, affecting the properties of the product. Therefore, the present invention, on the basis of setting three silicon carbide powders with different particle sizes, continues to control the content of each silicon carbide powder, which can make the formed silicon carbide ceramics denser, thereby further improving the product performance of the extruded silicon carbide material.

[0069] According to the extruded silicon carbide material of the present invention, the particle size of the carbon black is 100nm to 300nm; exemplary, the particle size of the carbon black is 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, 300nm. Carbon black has excellent wear resistance, and it is dispersed in the silicon carbide material, which can effectively reduce the wear of the silicon carbide blank, and the reasonable control of the particle size of the carbon black within a specific range can improve the lubrication performance of the surface of the silicon carbide blank, thereby further reducing the wear of the silicon carbide ceramic on the equipment.

[0070] According to the extruded silicon carbide material of the present invention, the dispersant includes at least one of polyethylene glycol and sodium dodecylbenzene sulfonate.

[0071] According to the extruded silicon carbide material of the present invention, the adhesive includes at least one of polyvinyl alcohol, phenolic resin and hydroxypropyl methylcellulose.

[0072] According to the extruded silicon carbide material of the present invention, the plasticizer includes a polysaccharide with a high degree of polymerization.

[0073] According to the extruded silicon carbide material of the present invention, the lubricant includes glycerin.

[0074] According to the extruded silicon carbide material of the present invention, the solvent is deionized water.

[0075] A second aspect of the present invention provides a method for preparing an extruded silicon carbide material, wherein the extruded silicon carbide material is the extruded silicon carbide material according to the first aspect of the present invention, and the method comprises the following steps:

[0076] The first step is to put the silicon carbide powder and the carbon black into a mixer and mix them for 1 hour to 2 hours;

[0077] The second step is to add the water reducing agent, the dispersant, the adhesive, the plasticizer, the lubricant and the solvent to the material obtained in the first step, and then knead the mixture for 1 to 3 hours using a kneader to obtain a slurry;

[0078] The third step is to age the clay obtained in the second step for more than 6 hours;

[0079] The fourth step is to use a vacuum mud making machine to make mud with the mud material aged in the third step;

[0080] The fifth step is to extrude the material obtained in the fourth step through an extruder and then dry it.

[0081] The third aspect of the present invention is the use of the extruded silicon carbide material described in the first aspect of the present invention or the extruded silicon carbide material prepared by the method for preparing the extruded silicon carbide material described in the second aspect of the present invention in the preparation of silicon carbide ceramics by reaction sintering or pressureless sintering.

[0082] In the present invention, a method for preparing silicon carbide ceramics by reaction sintering is also provided:

[0083] The first step is the heating process: the mold containing the green body formed by extrusion molding silicon carbide material is placed in the sintering furnace, and the temperature is slowly increased according to the set heating curve. The heating rate should be properly controlled to avoid cracking or other defects of the green body due to excessive heating;

[0084] The second step is the reaction stage: when the temperature reaches a certain value, a chemical reaction between the raw materials will be triggered. For example, in the reaction sintering of silicon carbide, silicon powder reacts with carbon to form silicon carbide. Control the reaction atmosphere and select a suitable atmosphere according to different reaction systems, such as inert atmospheres such as nitrogen and argon or specific reactive atmospheres;

[0085] The third step is the heat preservation process: keep the reaction temperature for a certain period of time to allow the reaction to proceed fully and ensure the stability of the product performance. The heat preservation time is determined according to factors such as the size of the product and the reaction system;

[0086] Step 4, cooling stage: After the reaction is completed, turn off the heating source and let the sintering furnace cool naturally or use a slow cooling method, such as controlling the cooling rate within a certain range to avoid excessive internal stress and cracking of the product caused by excessive cooling.

[0087] In the present invention, a method for preparing silicon carbide ceramics by pressureless sintering is also provided:

[0088] The first step is the heating process: the mold containing the green body formed by extrusion molding silicon carbide material is placed in the sintering furnace, and the temperature is slowly increased according to the set heating curve. The heating rate should be properly controlled to avoid cracking or other defects of the green body due to excessive heating;

[0089] The second step is sintering temperature and holding time: after reaching the predetermined sintering temperature, keep a certain holding time. The sintering temperature and holding time are determined according to factors such as the type of raw materials and the performance requirements of the product. For example, for some ceramic materials, the sintering temperature may be several thousand degrees Celsius and the holding time may be several hours;

[0090] The third step is atmosphere control: select a suitable sintering atmosphere according to the characteristics of the sintered material, such as air, nitrogen, argon and other inert atmospheres or specific oxidation and reduction atmospheres. The choice of atmosphere can affect the chemical reaction and material diffusion during the sintering process, thereby affecting the performance of the product;

[0091] Step 4, cooling stage: After the insulation is completed, turn off the heating source and let the sintering furnace cool naturally or slowly. Control the cooling rate to avoid excessive internal stress and cracking of the product caused by too fast cooling.

[0092] The extruded silicon carbide material provided by the present invention or the extruded silicon carbide material prepared by the preparation method of the present invention can be used to prepare silicon carbide ceramics by the above-mentioned reaction sintering method or pressureless sintering method.

[0093] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0094] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0095] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0096] In the following examples, unless otherwise specified, all components used were commercially available analytically pure. 1 part by weight represents 1 g.

[0097] Example 1

[0098] Used to prepare extruded silicon carbide materials

[0099] The components used in this implementation case are: by mass fraction of powder, 20 parts by weight of 80μm silicon carbide powder, 36 parts by weight of 50μm silicon carbide powder, 40 parts by weight of 17μm silicon carbide powder, 4 parts by weight of carbon black, 14 parts by weight of deionized water, 2.5 parts by weight of dispersant polyethylene glycol, 3 parts by weight of adhesive hydroxypropyl methylcellulose, 2.5 parts by weight of plasticizer high-polymerization degree polysaccharide, 2 parts by weight of water reducer (sulfonated polystyrene water reducer (sulfonic acid group content is 27%): polycarboxylic acid water reducer (carboxylic acid group content is 40%) = 1:1.9, at this time, the content of sulfonated polystyrene water reducer in the water reducer is 34.5%, and the content of polycarboxylic acid water reducer in the water reducer is 65.5%), and 0.5 parts by weight of lubricant glycerol.

[0100] The production steps of extruded silicon carbide materials are as follows:

[0101] In the first step, all the above silicon carbide powder and carbon black are put into a mixer and mixed for 1 hour;

[0102] In the second step, the mixed powder and the above-mentioned solvent, dispersant, adhesive, plasticizer, water reducing agent and lubricant are kneaded for 2 hours using a kneader;

[0103] The third step is to age the kneaded clay for more than 6 hours;

[0104] The fourth step is to use a vacuum mud making machine to make mud with the aged mud;

[0105] The fifth step is to extrude the prepared clay into products using an extruder;

[0106] Step 6: Place the extruded product in an oven for drying to obtain a green body formed by extrusion molding of silicon carbide material;

[0107] After the above drying step, the green body formed by extruding the silicon carbide material in this embodiment has no cracks and the clay is soft. Figure 1 , Figure 1 Figure a) is a cross-sectional angle view of the green body of the formed silicon carbide material. Figure 1 Figure b) is a side angle view of the green body of the formed silicon carbide material, and it can be seen that the green body made in Example 1 has no cracks.

[0108] Example 2-1

[0109] The components used in this embodiment are: by mass fraction of powder, 20 parts by weight of 80μm silicon carbide powder, 36 parts by weight of 50μm silicon carbide powder, 40 parts by weight of 17μm silicon carbide powder, 4 parts by weight of carbon black, 14 parts by weight of deionized water, 2.5 parts by weight of dispersant polyethylene glycol, 3 parts by weight of binder hydroxypropyl methylcellulose, 2.5 parts by weight of plasticizer high polymerization degree polysaccharide, 2 parts by weight of water reducer (sulfonated polystyrene water reducer: polycarboxylic acid water reducer = 1:1.1, at this time, the content of sulfonated polystyrene water reducer in the water reducer is 47.6%, the content of polycarboxylic acid water reducer in the water reducer is 52.4%, and the group content in the water reducer remains unchanged), and 0.5 parts by weight of lubricant glycerol.

[0110] The steps for making the extruded silicon carbide material are the same as those in Example 1;

[0111] After the above-mentioned drying step, the green body formed by extruding the silicon carbide material in the formulation of this embodiment has no cracks and the clay material is soft.

[0112] Example 2-2

[0113] The components used in this embodiment are: by mass fraction of powder, 20 parts by weight of 80μm silicon carbide powder, 36 parts by weight of 50μm silicon carbide powder, 40 parts by weight of 17μm silicon carbide powder, 4 parts by weight of carbon black, 14 parts by weight of deionized water, 2.5 parts by weight of dispersant polyethylene glycol, 3 parts by weight of binder hydroxypropyl methylcellulose, 2.5 parts by weight of plasticizer high polymerization degree polysaccharide, 2 parts by weight of water reducer (sulfonated polystyrene water reducer: polycarboxylic acid water reducer = 1:0.85, at this time, the content of sulfonated polystyrene water reducer in the water reducer is 54.6%, the content of polycarboxylic acid water reducer in the water reducer is 46.4%, and the group content in the water reducer remains unchanged), and 0.5 parts by weight of lubricant glycerol.

[0114] The steps for making the extruded silicon carbide material are the same as those in Example 1;

[0115] After the above-mentioned drying step, the green body formed by extruding the silicon carbide material in the formulation of this embodiment has no cracks and the clay material is soft.

[0116] Example 2-3

[0117] The components used in this embodiment are: by mass fraction of powder, 20 parts by weight of 80μm silicon carbide powder, 36 parts by weight of 50μm silicon carbide powder, 40 parts by weight of 17μm silicon carbide powder, 4 parts by weight of carbon black, 14 parts by weight of deionized water, 2.5 parts by weight of dispersant polyethylene glycol, 3 parts by weight of binder hydroxypropyl methylcellulose, 2.5 parts by weight of plasticizer high polymerization degree polysaccharide, 2 parts by weight of water reducer (sulfonated polystyrene water reducer: polycarboxylic acid water reducer = 1:2.2, at this time, the content of sulfonated polystyrene water reducer in the water reducer is 31.3%, the content of polycarboxylic acid water reducer in the water reducer is 68.8%, and the group content in the water reducer remains unchanged), and 0.5 parts by weight of lubricant glycerol.

[0118] The steps for making the extruded silicon carbide material are the same as those in Example 1;

[0119] After the above-mentioned drying step, the green body formed by extruding the silicon carbide material in the formulation of this embodiment has no cracks and the clay material is soft.

[0120] Example 3-1

[0121] The components used in this embodiment are: by mass fraction of powder, 20 parts by weight of 80μm silicon carbide powder, 36 parts by weight of 50μm silicon carbide powder, 40 parts by weight of 17μm silicon carbide powder, 4 parts by weight of carbon black, 14 parts by weight of deionized water, 2.5 parts by weight of dispersant polyethylene glycol, 3 parts by weight of binder hydroxypropyl methylcellulose, 2.5 parts by weight of plasticizer high polymerization degree polysaccharide, 3 parts by weight of water reducer (sulfonated polystyrene water reducer: polycarboxylic acid water reducer = 1:1.9, at this time, the content of sulfonated polystyrene water reducer in the water reducer is 34.5%, the content of polycarboxylic acid water reducer in the water reducer is 65.5%, and the group content in the water reducer remains unchanged), and 0.5 parts by weight of lubricant glycerol.

[0122] The steps for making the extruded silicon carbide material are the same as those in Example 1;

[0123] After the above-mentioned drying step, the green body formed by extruding the silicon carbide material in the formulation of this embodiment has no cracks and the clay material is soft.

[0124] Example 3-2

[0125] The components used in this embodiment are: by mass fraction of powder, 20 parts by weight of 80μm silicon carbide powder, 36 parts by weight of 50μm silicon carbide powder, 40 parts by weight of 17μm silicon carbide powder, 4 parts by weight of carbon black, 14 parts by weight of deionized water, 2.5 parts by weight of dispersant polyethylene glycol, 3 parts by weight of binder hydroxypropyl methylcellulose, 2.5 parts by weight of plasticizer high polymerization degree polysaccharide, 4 parts by weight of water reducer (sulfonated polystyrene water reducer: polycarboxylic acid water reducer = 1:1.9, at this time, the content of sulfonated polystyrene water reducer in the water reducer is 34.5%, the content of polycarboxylic acid water reducer in the water reducer is 65.5%, and the group content in the water reducer remains unchanged), and 0.5 parts by weight of lubricant glycerol.

[0126] The steps for making the extruded silicon carbide material are the same as those in Example 1;

[0127] After the above-mentioned drying step, the green body formed by extruding the silicon carbide material in the formulation of this embodiment has no cracks and the clay material is soft.

[0128] Example 4

[0129] The components used in this implementation case are: by mass fraction of powder, 20 parts by weight of 80μm silicon carbide powder, 36 parts by weight of 50μm silicon carbide powder, 40 parts by weight of 17μm silicon carbide powder, 4 parts by weight of carbon black, 14 parts by weight of deionized water, 2.5 parts by weight of dispersant polyethylene glycol, 3 parts by weight of adhesive hydroxypropyl methylcellulose, 2.5 parts by weight of plasticizer high polymerization degree polysaccharide, 2 parts by weight of water reducer (sulfonated polystyrene water reducer (sulfonic acid group content is 35%): polycarboxylic acid water reducer (carboxylic acid group content is 55%) = 1:1.9), at this time, the content of sulfonated polystyrene water reducer in the water reducer is 34.5%, and the content of polycarboxylic acid water reducer in the water reducer is 65.5%), and 0.5 parts by weight of lubricant glycerol.

[0130] The steps for making the extruded silicon carbide material are the same as those in Example 1;

[0131] After the above-mentioned drying step, the green body formed by extruding the silicon carbide material in the formulation of this embodiment has no cracks and the clay material is soft.

[0132] Example 5

[0133] The components used in this embodiment are: by mass fraction of powder, 96 parts by weight of 50μm silicon carbide powder, 4 parts by weight of carbon black, 14 parts by weight of deionized water, 2.5 parts by weight of dispersant polyethylene glycol, 3 parts by weight of binder hydroxypropyl methylcellulose, 2.5 parts by weight of plasticizer high polymerization degree polysaccharide, 2 parts by weight of water reducer (sulfonated polystyrene water reducer: polycarboxylic acid water reducer = 1:1.9, at this time, the content of sulfonated polystyrene water reducer in the water reducer is 34.5%, the content of polycarboxylic acid water reducer in the water reducer is 65.5%, and the group content in the water reducer remains unchanged), and 0.5 parts by weight of lubricant glycerol.

[0134] The steps for making the extruded silicon carbide material are the same as those in Example 1;

[0135] After the above-mentioned drying step, the green body formed by extruding the silicon carbide material in the formulation of this embodiment has no cracks and the clay material is soft.

[0136] Comparative Example 1

[0137] This comparative example was carried out with reference to Example 1, the only difference being that no water reducing agent was added to the raw material components of the extruded silicon carbide material.

[0138] The steps for making the extruded silicon carbide material are the same as those in Example 1;

[0139] After the above drying step, the green body formed by extruding the silicon carbide material cracked and the friction between the mud and the equipment was large. Figure 2 , Figure 2 Figure a) is a cross-sectional angle view of the green body of the formed silicon carbide material. Figure 2 Figure b) is a side angle view of the green body of the formed silicon carbide material, and it can be seen that the green body made in Comparative Example 1 is cracked.

[0140] Comparative Example 2

[0141] This comparative example is carried out with reference to Example 1, the only difference being that no sulfonated polystyrene water reducer is added to the raw material components of the extruded silicon carbide material.

[0142] The steps for making the extruded silicon carbide material are the same as those in Example 1;

[0143] After the above-mentioned drying step, the green body formed by the extruded silicon carbide material of this comparative example formula cracked and the friction between the mud material and the equipment was relatively large.

[0144] Comparative Example 3

[0145] This comparative example was carried out with reference to Example 1, except that no polycarboxylic acid water-reducing agent was added to the raw material components of the extruded silicon carbide material.

[0146] The steps for making the extruded silicon carbide material are the same as those in Example 1;

[0147] After the above-mentioned drying step, the green body formed by the extruded silicon carbide material of this comparative example formula cracked and the friction between the mud material and the equipment was relatively large.

[0148] Comparative Example 4

[0149] This comparative example is carried out with reference to Example 1, with the only difference being that the ratio of sulfonated polystyrene water reducer to polycarboxylic acid water reducer in the raw material components of the extruded silicon carbide material is 1:0.5, and at this time, the content of sulfonated polystyrene water reducer in the water reducer is 66.6%, and the content of polycarboxylic acid water reducer in the water reducer is 33.3%.

[0150] The steps for making the extruded silicon carbide material are the same as those in Example 1;

[0151] After the above-mentioned drying step, the green body formed by the extruded silicon carbide material of this comparative example formula cracked and the friction between the mud material and the equipment was relatively large.

[0152] Comparative Example 5

[0153] This comparative example is carried out with reference to Example 1, with the only difference being that the ratio of sulfonated polystyrene water reducer to polycarboxylic acid water reducer in the raw material components of the extruded silicon carbide material is 1:4, and at this time, the content of sulfonated polystyrene water reducer in the water reducer is 20%, and the content of polycarboxylic acid water reducer in the water reducer is 80%.

[0154] The steps for making the extruded silicon carbide material are the same as those in Example 1;

[0155] After the above-mentioned drying step, the green body formed by the extruded silicon carbide material of this comparative example formula cracked and the friction between the mud material and the equipment was relatively large.

[0156] Test Case

[0157] The extruded silicon carbide materials prepared in the above examples and comparative examples were subjected to a three-point bending strength test and a green body cracking test, and the test structures were finally recorded in Table 1.

[0158] (1) Three-point bending strength test: The specific operation steps are as follows:

[0159] The first step is sample preparation: According to the test standard requirements, the extruded silicon carbide material prepared in the above examples and comparative examples is prepared into a sample of a certain size and shape. Usually the sample is in the shape of a long strip, and the cross section can be rectangular, circular, etc. The sample is surface treated to ensure that the surface is smooth and has no obvious defects. In this test example, the sample prepared in the shape of a long strip with a circular cross section can be referred to Figure 1 and Figure 2 .

[0160] The second step is to install the specimen: place the specimen on the two supporting points of the three-point bending fixture, and adjust the spacing between the supporting points to meet the test standard requirements. Ensure that the specimen is in good contact with the supporting points and the loading points to avoid local stress concentration.

[0161] The third step is to conduct the test: start the universal testing machine and apply a concentrated load to the middle of the sample at a certain loading rate. Record the load and sample deformation in real time until the sample breaks.

[0162] Step 4: Data processing: Calculate the three-point bending strength of the material (in MPa) based on the maximum load recorded during the test and the geometric dimensions of the specimen.

[0163] (2) Green body cracking test: After the extruded silicon carbide materials prepared in the above embodiments and comparative examples are subjected to the above drying step, if cracks appear on the surface of the green body formed by the extruded silicon carbide materials, it is regarded as cracking. The above experimental steps are repeated 5 times, and the number of cracking times / number of experiments are recorded, and the number of cracking times = X, where X can be 0, 1, 2, 3, 4, or 5 times, and the number of experiments = 5 times.

[0164] Table 1

[0165] Group Three-point bending strength (MPa) Green cracking situation (times) Example 1 2.0954 0 / 5 Example 2-1 1.9232 0 / 5 Example 2-2 1.8016 1 / 5 Example 2-3 1.7921 1 / 5 Example 3-1 1.9993 0 / 5 Example 3-2 1.8645 0 / 5 Example 4 1.7333 1 / 5 Example 5 1.6987 2 / 5 Comparative Example 1 1.5664 5 / 5 Comparative Example 2 1.6033 4 / 5 Comparative Example 3 1.6404 4 / 5 Comparative Example 4 1.6523 4 / 5 Comparative Example 5 1.6641 4 / 5

[0166] From the analysis of Table 1, it can be seen that the green body formed by the extruded silicon carbide material prepared by the formula of the embodiment of the present invention has no cracking, and the number of cracking times of the sample is also low. Compared with the green body formed by the extruded silicon carbide material prepared by the formula of Comparative Example 1 without adding a water reducer, it has a lower breakage rate and a higher three-point bending strength. In addition, the material prepared by the embodiment of the present invention has a soft texture, and the green body also has certain lubrication and grinding aid effects, which can reduce the wear on the equipment, thereby saving energy consumption in product preparation.

[0167] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An extruded silicon carbide material, characterized in that: In parts by weight, it includes the following raw material components: 90 to 98 parts by weight of silicon carbide powder; 2 to 10 parts by weight of carbon black; 2 to 4 parts by weight of water reducing agent; 1.5 to 3.5 parts by weight of dispersant; 2 to 4 parts by weight of adhesive; 1.5 to 3.5 parts by weight of plasticizer; 0.2 to 0.8 parts by weight of lubricant; 10 to 20 parts by weight of solvent; Wherein, the water reducer includes sulfonated polystyrene water reducer and polycarboxylic acid water reducer; Based on the total mass of the water reducer, the content of the sulfonated polystyrene water reducer is 25% to 55%, and the content of the polycarboxylic acid water reducer is 45% to 75%.

2. The extruded silicon carbide material according to claim 1, characterized in that: Based on the total mass of the water reducer, the content of the sulfonated polystyrene water reducer is 28% to 42%, and the content of the polycarboxylic acid water reducer is 38% to 52%.

3. The extruded silicon carbide material according to claim 1, characterized in that: The mass ratio of the sulfonated polystyrene water reducer to the polycarboxylic acid water reducer is 1:(0.85-2.2), preferably 1:(1.1-1.9).

4. The extruded silicon carbide material according to claim 1, characterized in that: The content of sulfonic acid groups in the sulfonated polystyrene water reducer is 25% to 28%; The content of carboxylic acid groups in the polycarboxylic acid water-reducing agent is 30% to 50%.

5. The extruded silicon carbide material according to claim 4, characterized in that: The mass ratio of the sulfonic acid group to the carboxylic acid group in the water reducing agent is 1:(1.5-2.5); preferably 1:(1.8-2.2).

6. The extruded silicon carbide material according to claim 1, characterized in that: The particle size of the silicon carbide powder is 10 μm to 80 μm, and the silicon carbide powder includes a first silicon carbide powder, a second silicon carbide powder and a third silicon carbide powder; Wherein, the particle size of the first silicon carbide powder is 60 μm to 80 μm, the particle size of the second silicon carbide powder is 35 μm to 55 μm, and the particle size of the third silicon carbide powder is 5 μm to 25 μm.

7. The extruded silicon carbide material according to claim 6, characterized in that: Based on the total mass of the silicon carbide powder, the mass content of the first silicon carbide powder is 15% to 25%, the mass content of the second silicon carbide powder is 32.5% to 42.5%, and the mass content of the third silicon carbide powder is 37% to 46.5%.

8. The extruded silicon carbide material according to claim 1, characterized in that: The particle size of the carbon black is 100nm to 300nm; And / or, the dispersant includes at least one of polyethylene glycol and sodium dodecylbenzene sulfonate; And / or, the adhesive includes at least one of polyvinyl alcohol, phenolic resin, and hydroxypropyl methylcellulose; And / or, the plasticizer includes a high polymerization degree polysaccharide; and / or, the lubricant comprises glycerol; And / or, the solvent comprises deionized water.

9. A method for preparing an extruded silicon carbide material, characterized in that: The extruded silicon carbide material is the extruded silicon carbide material according to any one of claims 1 to 8, and the method comprises the following steps: The first step is to put the silicon carbide powder and the carbon black into a mixer and mix them for 1 hour to 2 hours; The second step is to add the water reducing agent, the dispersant, the adhesive, the plasticizer, the lubricant and the solvent to the material obtained in the first step, and then knead the mixture for 1 to 3 hours using a kneader to obtain a slurry; The third step is to age the clay obtained in the second step for more than 6 hours; The fourth step is to use a vacuum mud making machine to make mud with the mud material aged in the third step; The fifth step is to extrude the material obtained in the fourth step through an extruder and then dry it.

10. Use of the extruded silicon carbide material according to any one of claims 1 to 8 or the extruded silicon carbide material prepared by the method for preparing the extruded silicon carbide material according to claim 9 in preparing silicon carbide ceramics by reaction sintering or pressureless sintering.